(untitled) (Research, Society and Development, 2022)
Introduction: The diagnosis of breast cancer is performed by screening mammography. The BI-RADS (Breast Imaging Reporting and Data System) is an atlas launched by the American College of Radiology (ACR) to promote consistency and uniformity in breast imaging reports and comprises 07 categories, from 0 to 6. Methods: The study is retrospective and analytical-descriptive. It used the analysis of medical records and mammograms of patients with alterations referring to BIRADS-3, BIRADS-4 or BIRADS-5 treated at Hospital Geral Dr. César Cals de Oliveira (HGCC). Results: 445 reports were analyzed, with 422 reports referring to BIRADS-3 (B3), corresponding to 94.83% of the sample. Of the B3 findings, 59.72% of the reports have heterogeneously dense breasts, 31.75% have an oval shape and 31.75% have an irregular shape. Regarding the reported margins, 64.96% with lobulated margins; as for the density of the nodules, we have: 73.54% dense. Discussion: Breast cancer is the second most frequent cause of malignancy in women. Screening is the best secondary prevention methodology for the population. When analyzing the composition of the breasts with BIRADS 3, it was observed that most patients had heterogeneously dense breasts, which can obscure small masses (59.72%), requiring further examinations for better screening. Conclusion: It can be concluded that the results of the study were important to better understand the main mammographic findings with suspicious lesions according to the BI-RADS classification. It is also possible to highlight that the results are in agreement with the research already published in relation to the researched topic.